1980
DOI: 10.1007/bf01228303
|View full text |Cite
|
Sign up to set email alerts
|

Protection against streptozotocin-induced diabetes by superoxide dismutase

Abstract: Summary. Superoxide dismutase was administered intravenously to rats 50min prior to intravenous administration of a diabetogenic dose of streptozotocin. A dose of 45 mg/kg streptozotocin alone produced marked glucose intolerance and a decrease in pancreatic insulin content to less than 10% of control; both of these effects were abolished by prior administration of 105 u/g of superoxide dismutase. Superoxide dismutase (105 u/g) administered 50 min before 65 mg/kg intravenous streptozotocin did not prevent the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 12 publications
3
45
0
Order By: Relevance
“…Their mechanisms of action are unknown, but since their actions are inhibited by superoxide dismutase (SOD) [4,5] or a chemical scavenger, such as 1,1-dimethylurea [6], they have been suggested to be related to the formation of free radicals. In fact, some reports strongly support the participation of free radicals in the action of alloxan [7,8].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Their mechanisms of action are unknown, but since their actions are inhibited by superoxide dismutase (SOD) [4,5] or a chemical scavenger, such as 1,1-dimethylurea [6], they have been suggested to be related to the formation of free radicals. In fact, some reports strongly support the participation of free radicals in the action of alloxan [7,8].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…In vivo experiments show that transgenic mice with β cell-specific overexpression of Cu/Zn SOD are more resistant to alloxan-induced diabetes (11). Studies with rodents demonstrate that SOD administration can attenuate streptozotocin-induced (STZ-induced) hyperglycemia and diabetes (12)(13)(14). It was previously reported that antioxidant treatment exerts beneficial effects on β cell mass and insulin content in diabetic C57BL/KsJ-db/db mice (15).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes was assessed by IP glucose tolerance tests [6], following an overnight fast, 3 days after the injection of streptozotocin (50 mg/kg). Rats were maintained under light methoxyflurane anaesthesia throughout the glucose tolerance test.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of chemical and enzymatic oxygen radical scavengers have now been used for protection against both alloxan and streptozotocin effects in vitro and in vivo. Intravenous injection of copper-zinc superoxide dismutase before streptozotocin prevents diabetes in rats [6,7]. Partial protection against alloxan was obtained in mice using a polyethylene glycol derivative of superoxide dismutase [8].…”
mentioning
confidence: 99%